Ecologization: Barriers and Opportunities to Overcome Them in the Conditions of Post-War Recovery - KOSOVYCH, Bohdana; VASKIVSKA, Katerуna; KUCHER, Anatolii (Journal of Environmental Management and Tourism; Vol 13 No 7 (2022): JEMT, Volume XIII, Issue 7(63), Winter 2022, 2022)
The purpose of the scientific work is to identify objective and subjective obstacles to the successful development of ecologization as an important component of ensuring sustainable development and the direction of humanization of modern society, finding ways to overcome these obstacles using institutional tool. Based on the results of the research, the importance of intensifying the solution of environmental problems faced by modern humanity is argued. A complex of factors inhibiting the ecologically oriented efforts of the world community is identified. They are divided into objective and subjective obstacles. The essential characteristics of the isolated obstacles are considered. Attention is drawn to the environmental challenges caused by the military invasion of the russian occupiers in Ukraine. Possible ways of influencing the key institutions of society on the successful development of ecologization are proposed. The importance of ecologization as an innovative way of solving economic problems, preserving the environment and ensuring general well-being is established. The scientific novelty of the research results lies in the fact that, based on the definition of objective and subjective obstacles to the ecologization of all aspects of human existence, possible ways of influencing the key institutions of society – the state, politics, law, people, economy, entrepreneurship – on the establishment of ecological values have been clarified as decisive for humanity in the third millennium.